Habit persistence reduces risk aversion - Gollier, Christian (Geneva papers on risk and insurance. Issues and practice, 2021)
How does habit formation affect the dynamic demand for insurance and risky assets? We examine a dynamic portfolio-saving choice problem for two structures of preferences. In the first model, the consumer faces an exogenous path of minimum levels of subsistence over time. In the second model, these levels are subject to habit persistence, i.e. they are increasing in past consumption. We show that adding habit persistence to the initial model substantially reduces the aversion to risk. The intuition is that the positive correlation between current portfolio returns and future levels of subsistence helps time-diversifying risks. This result goes against the wide-spread idea that habit persistence can resolve the equity premium puzzle.